Let's Make Language Learning a Meaningful Experience: Theme Based Teaching for Fourth Graders (2017)
ABSTRACT: Theme-based teaching was proven to be very useful for fostering meaningful language learning because this approach provides the opportunity to balance content and language. Meaningful language experiences emerge when students begin to express their interests using their previous knowledge and connect the class content with their lives. Three data collection techniques were used not only to answer the research question, but to achieve the objectives of this project. A journal to describe each given lesson. An interview to the Cooperating teacher and a survey to students. This study concluded that theme-based teaching makes language learning experience meaningful when students’ needs and interest are considered as the foundations upon which lesson planning should depart.